Differential impact of diverse anticancer chemotherapeutics on the Cdc25A-degradation checkpoint pathway - Agner, J; Falck, J; Lukáš, Jiří; Bártek, Jiří (Experimental cell research, 2005)
When exposed to DNA-damaging insults such as ionizing radiation (IR) or ultraviolet light (UV), mammalian cells activate checkpoint pathways to halt cell cycle progression or induce cell death. Here we examined the ability of five commonly used anticancer drugs with different mechanisms of action to activate the Chk1/Chk2-Cdc25A-CDK2/cyclin E cell cycle checkpoint pathway, previously shown to be induced by IR or UV. Whereas exposure of human cells to topoisomerase inhibitors camptothecin, etoposide, or adriamycin resulted in rapid (within 1 h) activation of the pathway including degradation of the Cdc25A phosphatase and inhibition of cyclin E/CDK2 kinase activity, taxol failed to activate this checkpoint even after a prolonged treatment. Unexpectedly, although the alkylating agent cisplatin also induced degradation of Cdc25A (albeit delayed, after 8-12 h), cyclin E/CDK2 activity was elevated and DNA synthesis continued, a phenomena that correlated with increased E2F1 protein levels and consequently enhanced expression of cyclin E. These results reveal a differential impact of various classes of anticancer chemotherapeutics on the Cdc25A-degradation pathway, and indicate that the kinetics of checkpoint induction, and the relative balance of key components within the DNA damage response network may dictate whether the treated cells arrest their cell cycle progression.
Keywords: Checkpoint Kinase 2; Cell Line, Transformed; doxorubicin; transformované buněčné linie; poškození DNA; protein-serin-threoninkinasy; monoklonální protilátky; osteosarkom; Enzyme Activation; Radiation, Ionizing; checkpoint kinasa 2; Antineoplastic Agents, Phytogenic; protinádorová antibiotika; Topoisomerase I Inhibitors; DNA Damage; Cell Line, Tumor; Protein Serine-Threonine Kinases; ionizující záření; inhibitory topoisomerasy I; kamptothecin; proteinkinasy; inhibitory topoisomerasy II; Osteosarcoma; etoposid; paclitaxel; Camptothecin; Flow Cytometry; Paclitaxel; ultrafialové záření; kinetika; Protein Kinases; průtoková cytometrie; cdc25 Phosphatases; lidé; Humans; cyklin E; Antibiotics, Antineoplastic; Cell Cycle; Ultraviolet Rays; DNA; aktivace enzymů; cisplatina; fosfatasy cdc25; Antibodies, Monoclonal; buněčný cyklus; Cyclin E; nádorové buněčné linie; fytogenní protinádorové látky; Cisplatin; Topoisomerase II Inhibitors; Kinetics; Doxorubicin; Etoposide